A Decentralized Electronic Reporting Scheme with Privacy Protection Based on Proxy Signature and Blockchain. (7th February 2022) - Zou, Huiying; Liu, Xiaofan; Ren, Wei; Zhu, Tianqing
Abstract : The electronic reporting system can alleviate the problems in terms of efficiency, content confidentiality, and reporter privacy imposed in the traditional reporting system. Relying on anonymity, the privacy of reporters can be protected, but the authentication of reporters with fake names should also be maintained. If authenticated anonymity is guaranteed, the reporters may still conduct misbehaviors such as submitting fake reports after the authentication. To address the above dilemma, we propose to apply a proxy signature to achieve authenticated anonymity and employ blockchain to maintain anonymity yet guarantee traceability for reporters' misbehaviors. We also propose a new proxy signature scheme in this paper by module lattice for postquantum security. The extensive analysis justified our proposed scheme is secure and manageable.